STRATEGI PUBLIC RELATIONS MELALUI KEGIATAN PRESS TOUR PADA PROGRAM KERJA WISATA BAHARI DALAM MEMBANGUN CITRA PT. PELNI (PERSERO) - Astri Dwi Ramadhani (Universitas Mercu Buana, 2015)
The problem in this research is negative report related PT. PELNI (Persero) about the loss of the company. The existence of Low Cost Carrier (LCC) which makes the image of PT. PELNI (Persero) faded as many passengers aboard ships to aircraft. Subjects in this study consist of internal and external parties. From internal parties, namely Corporate Secretary, Public Relations, and Marketing Manager of PT. PELNI (Persero). While from external parties namely Journalist and User Services. The research method used is case study method with qualitative approach. Researchers use this method because of research questions pertaining to